The Community Residents’Participation in the Development of Sufficiency Economy Village: A Case Study of Hua Dong Sub district, Mueang District, Phichit Province - Kalayanamitra, Keratiwan; Jakkapattarawong, Sunhanat; Srison, Wijittra (Rajapark Journal, 2020)
These research objectives are: 1) to study the level of people's participation in the development of the sufficiency economy village of Hua Dong Subdistrict, Mueang District, Phichit Province 2) to study the relationship between the level of people's participation and personal factors as well as environmental factors, and 3) to study the problems, obstacles, and suggestions regarding public participation. This study uses mixed research methods. The method used to collect qualitative data was an in-depth interview with community administrators, community developers, and group leaders in the community. The method used to collect quantitative data was a survey with a structured questionnaire distributed among 364 residents of Hua Dong Subdistrict. The sampling procedure was conducted by using prefabricated tables of Krejcie, R. V. & Morgan, D. W. Data. Descriptive statistics and inferential statistics were employed to analyze the data. The research results are as follows. People in the Sufficiency Economy Village participate in the overall village development at a high level. Some of the personal factors are not related to the level of participation. However, they are related to opinions about development. Problems and obstacles relating to public participation include people lacking knowledge and understanding about participation in operating, monitoring, and evaluating various activities or projects.